Sunscreen raw material and preparation method thereof and cosmetics

By using a porous matrix carrier to wrap the sunscreen and form bonds with the functional groups on the surface of the carrier, the existing sunscreen agents are solved, and the problems of insufficient sunscreen capacity and risk of skin inhalation are achieved, achieving more efficient sunscreen effects and safer use.

CN116211722BActive Publication Date: 2025-04-15GUANGDONG MARUBI BIOLOGICAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211689295.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-27
Publication Date
2025-04-15
Estimated Expiration
2042-12-27

AI Technical Summary

Technical Problem

The existing use of inorganic and organic sunscreens in cosmetics has problems such as insufficient sunscreen ability, easy clogging of pores and skin irritation, and sunscreens are easily inhaled by the skin, resulting in potential damage.

Method used

The sunscreen is wrapped with a porous matrix carrier. By arranging the sunscreen in the porous structure of the porous matrix carrier and forming physical and chemical bonds with the functional groups on the surface of the carrier, the wrapping firmness and sun protection ability of the sunscreen are improved.

Benefits of technology

It significantly improves the sunscreen ability of sunscreen, reduces the risk of sunscreen being inhaled by the skin, and avoids the damage such as irritation and oxidation of sunscreen to the skin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116211722B_ABST
    Figure CN116211722B_ABST
Patent Text Reader

Abstract

The present application relates to the field of cosmetics, and to a sunscreen raw material, a preparation method thereof, and cosmetics. The sunscreen raw material includes a porous matrix carrier and a sunscreen agent; the surface of the porous matrix carrier is modified with functional groups. The sunscreen agent is accommodated in the pore structure of the porous matrix carrier, and the sunscreen agent and the functional groups have physical and chemical bonding. The porous structure of the porous matrix carrier effectively and evenly wraps the sunscreen agent, significantly improving the sunscreen ability of the sunscreen agent while reducing the risk of the sunscreen agent being inhaled by the skin, and is expected to avoid the risk of sunscreen agent irritating the skin, oxidizing, and other damages. Since the sunscreen agent can physically and chemically bond with the functional groups on the surface of the porous matrix carrier, the firmness of the porous matrix carrier to the sunscreen agent is greatly improved, so that the sunscreen agent can be firmly accommodated in the porous structure of the porous matrix carrier, and it is not easy to fall off from the porous matrix carrier, thereby ensuring a reliable wrapping effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of cosmetics, and in particular, to a sunscreen raw material, a preparation method thereof, and cosmetics. Background Art

[0002] Ultraviolet rays are a general term for radiation with a wavelength of 400~10nm in a vacuum. They are invisible light. When ultraviolet rays irradiate the human body, they can promote the synthesis of vitamin D in the human body and have antibacterial and anti-inflammatory effects. However, excessive exposure to ultraviolet rays can cause a variety of skin problems. Usually, ultraviolet rays are mainly divided into three sections according to different bands: UVA zone: low-frequency long-wave, with a wavelength range of 400~320nm. UVA can not only reach the surface of the skin and cause sunburn, redness and pain, but also penetrate into the dermis of the skin, causing the skin to tan; UVB zone: medium-frequency medium-wave, with a wavelength range of 320~280nm. Most of this type of ultraviolet rays are absorbed by the epidermis of the skin and cannot penetrate into the skin. However, long-term exposure can cause skin erythema, inflammation and skin aging. It is an ultraviolet band that needs to be focused on; UVC zone: high-frequency short-wave, with a wavelength range of 280~100nm. Ultraviolet rays in this band will be absorbed by the ozone layer and cannot reach the earth's surface. Therefore, sunscreen products involved in the cosmetics field need to focus on protecting against UVA and UVB ultraviolet rays, because such ultraviolet rays can cause sunburn, tanning, erythema and other skin problems to the human skin.

[0003] According to the requirements of the 2015 edition of the "Technical Specifications for Safety of Cosmetics", sunscreens can be divided into two categories: inorganic sunscreens and organic sunscreens. Inorganic sunscreens are a type of white inorganic mineral powder. Currently, only titanium dioxide and zinc oxide are allowed to be used. The sunscreen mechanism of inorganic sunscreens is related to the size of its powder particles. When the powder particle size is large, it reflects and scatters the irradiated ultraviolet rays, achieving the effect of a physical barrier, with weak sunscreen ability and easy clogging of pores; when the powder particle size is small, the reflection and scattering ability of ultraviolet rays is weakened, the absorption capacity is enhanced, and the sunscreen ability is enhanced, but this type of sunscreen is prone to produce free radicals to oxidize the skin. Organic sunscreens are a type of organic compound that has a good absorption effect on ultraviolet rays. This type of sunscreen converts the absorbed ultraviolet rays into heat energy, and its own structure does not change. However, there are many safety hazards in organic sunscreens, such as irritating the skin and causing skin allergies. Existing products generally improve the sun protection ability of inorganic and organic sunscreens by increasing the dosage of sunscreens. This requires adding a large amount of oil to the sunscreen products to dissolve the sunscreens, resulting in a poor skin feel and increased safety risks.

[0004] In order to solve the problems encountered by existing inorganic and organic sunscreens, Guangdong MaruMei Biotechnology Co., Ltd. has developed a method for preparing hollow mesoporous silica microspheres loaded with sunscreen (CN109160519A). However, the sunscreen prepared by this method is prone to leak out of the matrix carrier during the use of cosmetic products, thereby losing the significance of loading. Summary of the invention

[0005] The purpose of the embodiments of the present application is to provide a sunscreen raw material, a preparation method thereof, and cosmetics.

[0006] In a first aspect, the present application provides a sunscreen raw material, comprising:

[0007] A porous matrix carrier and a sunscreen; the surface of the porous matrix carrier is modified with functional groups;

[0008] The sunscreen agent is contained in the pore structure of the porous matrix carrier, and the sunscreen agent is physically and chemically bonded to the functional groups.

[0009] The sunscreen raw material of the present application, by accommodating the sunscreen in the pore structure of the porous matrix carrier, due to the larger specific surface area of ​​the porous matrix carrier, through the design of the functional groups on the surface of the porous matrix carrier, the wrapped object (sunscreen) can be evenly dispersed in the pore structure, thereby achieving the effect of the porous structure of the porous matrix carrier effectively and evenly wrapping the sunscreen. Further, the molecular weight of the sunscreen currently used on the market is very small, and it is easy to enter the human body through the skin pores such as hair follicles, causing harm. The sunscreen raw material of the present application, using a porous matrix carrier to wrap the sunscreen, the agent wraps up the small molecule substance to avoid the small molecule sunscreen from directly contacting the skin, which can not only significantly improve the sunscreen ability of the sunscreen, but also reduce the risk of the sunscreen being inhaled by the skin, thereby hopefully avoiding the risk of sunscreen irritation, oxidation and other damage to the skin.

[0010] Furthermore, the sunscreen raw materials of the present application greatly improve the firmness of the porous matrix carrier's encapsulation of the sunscreen because the sunscreen agent can physically and chemically bond with the functional groups on the surface of the porous matrix carrier, so that the sunscreen agent can be firmly contained in the porous structure of the porous matrix carrier and is not easy to fall off from the porous matrix carrier, thereby ensuring a reliable encapsulation effect, and further ensuring that the sunscreen ability of the sunscreen agent is stably improved while reducing the risk of the sunscreen agent being absorbed into the skin, thereby hopefully avoiding the risks of skin damage such as irritation and oxidation caused by the sunscreen agent.

[0011] In other embodiments of the present application, the functional group includes at least one of a carboxylic acid group, a sulfonic acid group, an amino group or a siloxane group.

[0012] In other embodiments of the present application, the porous matrix carrier comprises: porous TiO2 , porous SiO 2 , porous ZnO or at least one of silicon-aluminum molecular sieves.

[0013] In other embodiments of the present application, the sunscreen comprises: at least one of an inorganic sunscreen or an organic sunscreen; optionally, the inorganic sunscreen comprises TiO 2 Or at least one of ZnO; optionally, the organic sunscreen includes at least one of benzophenone-3, butyl methoxydibenzoylmethane, diethylaminohydroxybenzoyl hexyl benzoate, octocrylene or ethylhexyl 4-methoxycinnamate.

[0014] In other embodiments of the present application, in the sunscreen raw materials, the mass percentage of the sunscreen agent is 10% to 80%, and the remainder is the porous matrix carrier.

[0015] In a second aspect, the present application provides a method for preparing a sunscreen raw material, comprising:

[0016] The sunscreen agent is contained in the pore structure of the porous matrix carrier whose surface is modified with functional groups, and the sunscreen agent is physically and chemically bonded with the functional groups.

[0017] In other embodiments of the present application, a porous matrix carrier with a surface modified with functional groups is prepared, comprising:

[0018] A template is used to synthesize a porous matrix carrier with different pore structures, and functional groups are modified on the surface of the porous matrix carrier;

[0019] Optionally, the template agent includes: any one of an anionic surfactant, a cationic surfactant, a nonionic surfactant or a block copolymer;

[0020] Optionally, the anionic surfactant includes sodium lauroyl sarcosinate; optionally, the cationic surfactant includes hexadecyltrimethylammonium bromide; optionally, the nonionic surfactant includes Tween-80; optionally, the block copolymer includes polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer.

[0021] In other embodiments of the present application, functional group modification is performed on the surface of the porous matrix carrier, including:

[0022] The porous matrix support is mixed with a functional group precursor solution.

[0023] In other embodiments of the present application, the sunscreen is contained in the pore structure of a porous matrix carrier with a surface modified with functional groups, comprising:

[0024] The porous matrix carrier is mixed with a sunscreen solution; optionally, the solvent of the sunscreen solution includes at least one of ethanol, acetone, DMSO, dimethyl sulfoxide or ether.

[0025] In a third aspect, the present application provides a cosmetic comprising the sunscreen raw material provided in the first or second aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 The surface carboxylic acid-modified porous SiO prepared in Example 1 2 A comparison chart of the ultraviolet transmittance of the sunscreen raw material encapsulating diethylaminohydroxybenzoyl hexyl benzoate and the sunscreen raw material provided in Comparative Example 4. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0029] Therefore, the following detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0030] The present application embodiment provides a sunscreen raw material, including:

[0031] A porous matrix carrier and a sunscreen; the surface of the porous matrix carrier is modified with functional groups;

[0032] The sunscreen agent is contained in the pore structure of the porous matrix carrier, and the sunscreen agent is physically and chemically bonded to the functional groups.

[0033] The sunscreen raw material provided in the embodiment of the present application can undergo physical and chemical bonding with the functional groups on the surface of the porous matrix carrier, that is, the sunscreen can undergo both chemical bonding and material bonding with the functional groups on the surface of the porous matrix carrier. This greatly improves the firmness of the porous matrix carrier's wrapping of the sunscreen, allowing the sunscreen to be firmly contained in the porous structure of the porous matrix carrier and not easily fall off from the porous matrix carrier, thereby ensuring a reliable wrapping effect, and further ensuring that the sunscreen ability of the sunscreen can be stably improved while reducing the risk of the sunscreen being absorbed into the skin, thereby hopefully avoiding the risks of skin damage such as irritation and oxidation caused by the sunscreen.

[0034] Furthermore, in some embodiments of the present application, the functional group includes at least one of a carboxylic acid group, a sulfonic acid group, an amino group or a siloxane group.

[0035] Further, in some embodiments of the present application, the porous matrix carrier comprises: porous TiO 2 , porous SiO 2 , porous ZnO or at least one of silicon-aluminum molecular sieves.

[0036] Furthermore, in some embodiments of the present application, the porous structure of the matrix carrier is a combination of one or more of micropores, mesopores, macropores and multi-level pores.

[0037] Further, in some embodiments of the present application, the sunscreen comprises: at least one of an inorganic sunscreen or an organic sunscreen; optionally, the inorganic sunscreen comprises TiO 2 Or at least one of ZnO; optionally, the organic sunscreen includes at least one of benzophenone-3, butyl methoxydibenzoylmethane, diethylaminohydroxybenzoyl hexyl benzoate, octocrylene or ethylhexyl 4-methoxycinnamate.

[0038] It should be noted that when the inorganic sunscreen agent is TiO 2 The porous matrix support is preferably porous SiO 2 , porous ZnO or silicon-aluminum molecular sieve.

[0039] Furthermore, in some embodiments of the present application, in the sunscreen raw materials, the mass percentage of the sunscreen agent is 10% to 80%, and the remainder is the porous matrix carrier.

[0040] Further optionally, in some embodiments of the present application, in the sunscreen raw materials, the mass percentage of the sunscreen agent is 11% to 79%, and the remainder is the porous matrix carrier.

[0041] Exemplarily, in the sunscreen raw materials, the mass proportion of sunscreen agent is 10%, and the porous matrix carrier is 90%; or the mass proportion of sunscreen agent is 15%, and the porous matrix carrier is 85%; or the mass proportion of sunscreen agent is 20%, and the porous matrix carrier is 80%; or the mass proportion of sunscreen agent is 30%, and the porous matrix carrier is 70%; or the mass proportion of sunscreen agent is 50%, and the porous matrix carrier is 50%; or the mass proportion of sunscreen agent is 60%, and the porous matrix carrier is 40%; or the mass proportion of sunscreen agent is 70%, and the porous matrix carrier is 30%.

[0042] Some embodiments of the present application provide a method for preparing a sunscreen raw material, comprising:

[0043] The sunscreen agent is contained in the pore structure of the porous matrix carrier whose surface is modified with functional groups, and the sunscreen agent is physically and chemically bonded with the functional groups.

[0044] Furthermore, in some embodiments of the present application, the method for preparing the sunscreen raw material comprises the following steps:

[0045] Step S1, preparing a porous matrix carrier.

[0046] Further, in some embodiments of the present application, preparing a porous matrix carrier comprises:

[0047] Templates are used to synthesize porous matrix supports with different pore structures.

[0048] Specifically, a template is used to synthesize a matrix carrier with different pore structures through different self-assembly methods.

[0049] Furthermore, in some embodiments of the present application, the above-mentioned template includes: any one of anionic surfactants, cationic surfactants, nonionic surfactants or block copolymers.

[0050] Further optionally, the above-mentioned anionic surfactant includes: sodium lauroyl sarcosinate; optionally, the cationic surfactant includes: cetyltrimethylammonium bromide; optionally, the nonionic surfactant includes: Tween-80; optionally, the block copolymer includes: polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer.

[0051] In other words, the template is selected from any one of anionic surfactants represented by sodium lauroyl sarcosinate (Sar-Na), cationic surfactants represented by cetyltrimethylammonium bromide (CTAB), nonionic surfactants represented by Tween-80, or block copolymers represented by polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123).

[0052] Further, in some embodiments of the present application, the method for preparing a matrix carrier with different pore structures includes:

[0053] The precursor for preparing the porous matrix carrier is slowly added dropwise to the template solution, and then stirred under water bath heating conditions to carry out a hydrothermal reaction. After the reaction is completed, the reaction product is separated, washed, dried, and calcined to obtain the porous matrix carrier.

[0054] Furthermore, in some embodiments of the present application, the template solution is prepared by dissolving the template into a uniform solution using a solvent.

[0055] Furthermore, in some embodiments of the present application, the solution for dissolving the template includes any one or more combinations of small molecule solvents such as water, ethanol, acetylacetone, acetone, etc.

[0056] Furthermore, in some embodiments of the present application, the precursor for preparing the porous matrix carrier includes: any one of a silicon source represented by TEOS, a titanium source represented by titanium isopropoxide, an aluminum source represented by aluminum isopropoxide, and a zinc source represented by zinc nitrate.

[0057] Furthermore, in some embodiments of the present application, the temperature of the water bath heating and stirring is 25~80°C.

[0058] Further, in some embodiments of the present application, the time of heating and stirring in a water bath is 5 h to 30 h. Further optionally, the time of heating and stirring in a water bath is 6 h to 29 h. Exemplarily, the time of heating and stirring in a water bath is 7 h, 10 h, 15 h, 20 h, 25 h or 28 h.

[0059] Further, in some embodiments of the present application, the hydrothermal reaction temperature is 50° C. to 150° C. Further optionally, the hydrothermal reaction temperature is 51° C. to 149° C. Exemplarily, the hydrothermal reaction temperature is 55° C., 60° C., 80° C., 100° C., 120° C. or 140° C.

[0060] Further, in some embodiments of the present application, the hydrothermal reaction time is 5 h to 40 h. Further optionally, in some embodiments of the present application, the hydrothermal reaction time is 6 h to 39 h. Exemplarily, the hydrothermal reaction time is 8 h, 10 h, 15 h, 20 h, 25 h, 30 h or 35 h.

[0061] Step S2: modifying the surface functional groups of the porous matrix carrier.

[0062] Furthermore, in some embodiments of the present application, the porous matrix carrier is subjected to surface functional group modification, comprising:

[0063] The porous matrix support prepared in step S1 is mixed with the functional group precursor solution.

[0064] Furthermore, in some embodiments of the present application, the method for modifying the surface functional groups of the porous matrix carrier to carboxyl modification is:

[0065] A certain amount of KH-550 and succinic anhydride are dispersed in an organic solvent, and magnetically stirred for a certain time at a certain temperature. Then, a porous matrix carrier dispersed in the organic solvent is added to the above system. After continuing magnetic stirring for a certain time, centrifugation, separation and drying are performed to obtain a porous material matrix carrier with surface carboxylation.

[0066] Furthermore, in other optional embodiments of the present application, the modification of sulfonic acid group, amino group or siloxane group on the surface of the porous matrix carrier can also be obtained by selecting corresponding modification molecules to chemically bond with hydroxyl groups or unsaturated residual bonds on the surface of the porous matrix carrier.

[0067] Furthermore, in some embodiments of the present application, the organic solvent includes at least one of DMF, dimethyl sulfoxide, ethanol or diethyl ether.

[0068] Further, in some embodiments of the present application, the porous matrix carrier is porous TiO 2 , porous SiO 2 , porous ZnO or at least one of silicon-aluminum molecular sieves.

[0069] Furthermore, in some embodiments of the present application, the above temperature is 30°C~30°C.

[0070] Further, in some embodiments of the present application, the reaction time is 3 h to 5 h. Exemplarily, the reaction time is 3 h, 3.5 h, 4 h, 4.5 h or 5 h.

[0071] Step S3: placing the sunscreen in the pore structure of the porous matrix carrier with the surface modified with functional groups, and making the sunscreen physically or chemically bonded with the functional groups.

[0072] Placing the sunscreen in the pore structure of a porous matrix carrier with a surface modified with functional groups may also be referred to as the porous matrix carrier encapsulating the sunscreen.

[0073] Furthermore, in some embodiments of the present application, the sunscreen is contained in the pore structure of the porous matrix carrier with the surface modified with functional groups, and the sunscreen is physically or chemically bonded with the functional groups, including:

[0074] The porous matrix carrier with functional groups on its surface prepared in step S2 is mixed with the sunscreen solution and stirred so that the sunscreen is accommodated in the pore structure of the porous matrix carrier with functional groups on its surface and the sunscreen is physically or chemically bonded with the functional groups; post-treatment is then performed, followed by drying and calcination to remove the solvent.

[0075] Furthermore, in some embodiments of the present application, the solvent of the sunscreen solution includes one or more combinations of small molecule solvents such as ethanol, acetone, DMSO, dimethyl sulfoxide or ether.

[0076] Furthermore, in some embodiments of the present application, the sunscreen includes an inorganic sunscreen and an organic sunscreen.

[0077] Furthermore, in some embodiments of the present application, the precursor of the inorganic sunscreen agent includes: any one of a titanium source represented by titanium isopropoxide and a zinc source represented by zinc nitrate.

[0078] Further, in some embodiments of the present application, the organic sunscreen includes: a combination of one or more of benzophenone-3, butyl methoxydibenzoylmethane, diethylaminohydroxybenzoyl hexyl benzoate, octocrylene or ethylhexyl 4-methoxycinnamate.

[0079] In other optional embodiments of the present application, the above-mentioned organic sunscreen agent may also be selected from other common organic sunscreen agents in the art.

[0080] Furthermore, in some embodiments of the present application, when the sunscreen is contained in the pore structure of the porous matrix carrier with a surface modified with functional groups, the sunscreen accounts for 10% to 80% by mass, and the remainder is the porous matrix carrier. For example, the sunscreen accounts for 20% and the porous matrix carrier accounts for 80%.

[0081] Further, in some embodiments of the present application, the stirring temperature when mixing the porous matrix carrier with functional groups on the surface prepared in step S2 with the sunscreen solution is 25°C to 80°C. Further optionally, the stirring temperature is 30°C to 75°C; illustratively, the stirring temperature is 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C or 75°C.

[0082] Furthermore, in some embodiments of the present application, the stirring time when mixing the porous matrix carrier with functional groups on the surface obtained in step S2 with the sunscreen solution is 5 h to 30 h; further optionally, the stirring time is 6 h to 29 h; illustratively, the stirring time is 7 h, 8 h, 10 h, 12 h, 15 h, 18 h, 20 h, 22 h, 25 h or 28 h.

[0083] Furthermore, in some embodiments of the present application, the above-mentioned post-treatment method includes one or more combinations of centrifugation, filtration or rotary evaporation.

[0084] Further, in some embodiments of the present application, the drying or calcining temperature is 50° C. to 550° C. Further optionally, in some embodiments of the present application, the drying or calcining temperature is 80° C., 100° C., 200° C., 300° C., 400° C. or 500° C.

[0085] Some embodiments of the present application provide a cosmetic comprising the sunscreen raw material provided by any of the aforementioned embodiments.

[0086] The cosmetics of the present application, by comprising the sunscreen raw materials provided by any of the aforementioned embodiments, the sunscreen is contained in the pore structure of the porous matrix carrier, thereby achieving the effect that the porous structure of the porous matrix carrier effectively and evenly wraps the sunscreen, which can not only significantly improve the sunscreen ability of the sunscreen but also reduce the risk of the sunscreen being absorbed by the skin, thereby hopefully avoiding the risks of sunscreen irritation, oxidation and other damages to the skin.

[0087] Furthermore, the cosmetics of the present application, since the sunscreen agent can physically or chemically bond with the functional groups on the surface of the porous matrix carrier, the firmness of the porous matrix carrier's encapsulation of the sunscreen agent is greatly improved, so that the sunscreen agent can be firmly contained in the porous structure of the porous matrix carrier and is not easy to fall off from the porous matrix carrier, thereby ensuring a reliable encapsulation effect, and further ensuring that the sunscreen ability of the sunscreen agent is stably improved while reducing the risk of the sunscreen agent being absorbed into the skin, thereby hopefully avoiding the risks of sunscreen agent causing irritation, oxidation and other damage to the skin.

[0088] The features and performance of the present application are further described in detail below in conjunction with the embodiments:

[0089] Example 1

[0090] Provided is a sunscreen raw material, which is prepared according to the following steps:

[0091] Step 1: Weigh 20 g of P123 into a round-bottom flask, add 400 ml of 2.0 M HCl solution to dissolve into a uniform solution, then slowly drop TEOS, stir in a 40 ° C water bath for 30 min, react at 100 ° C for 24 h, separate, wash, dry, and calcine to obtain SiO with a hexagonal mesoporous structure. 2 Matrix carrier. Equimolar KH-550 and succinic anhydride were uniformly dispersed in 50 ml DMF, and magnetically stirred at 50 °C for 3 h. Then, 20 ml of porous SiO2, which had been ultrasonically dispersed for 10 min, was added to the system. 2 The matrix carrier DMF solution was stirred for 5 h, centrifuged, washed and dried to obtain porous SiO2 modified with surface carboxyl groups.2 Matrix carrier.

[0092] Step 2: The surface carboxyl-modified SiO2 with hexagonal mesoporous structure prepared in step 1 2 5 g of the matrix carrier was placed in a pear-shaped bottle, and 100 ml of an ethanol solution containing 5 g of diethylaminohydroxybenzoyl benzoic acid hexyl ester was added. The mixture was stirred at 50 ° C for 24 h, rotary evaporated at 40 ° C for 2 h, and dried for 24 h to obtain a porous SiO2 with surface carboxyl modification. 2 Packed with diethylamino hydroxybenzoyl hexyl benzoate sunscreen.

[0093] Example 2

[0094] Provided is a sunscreen raw material, which is prepared according to the following steps:

[0095] Step 1: Weigh 20 g of P123 into a round-bottom flask, add 400 ml of 2.0 M HCl solution to dissolve into a uniform solution, then slowly drop TEOS, stir in a 40 ° C water bath for 30 min, react at 100 ° C for 24 h, separate, wash, dry, and calcine to obtain SiO with a hexagonal mesoporous structure. 2 Matrix carrier. Equimolar KH-550 and succinic anhydride were uniformly dispersed in 50 ml DMF, and magnetically stirred at 50 °C for 3 h. Then, 20 ml of porous SiO2 that had been ultrasonically dispersed for 10 min was added to the system. 2 The matrix carrier DMF solution was stirred for 5 h, centrifuged, washed and dried to obtain porous SiO2 modified with surface carboxyl groups. 2 Matrix carrier.

[0096] Step 2: The surface carboxyl-modified SiO2 with hexagonal mesoporous structure prepared in step 1 2 5 g of the matrix carrier was placed in a pear-shaped bottle, and 100 ml of an ethanol solution containing 20 g of isopropyl titanate was added. The mixture was stirred at 50 °C for 24 h, rotary evaporated at 40 °C for 2 h, dried for 24 h, and calcined at 450 °C for 2 h to obtain a porous SiO2 with surface carboxyl modification. 2 Wrapping TiO 2 Sunscreen.

[0097] Example 3

[0098] Provided is a sunscreen raw material, which is prepared according to the following steps:

[0099] Weigh 15g P123 in a round-bottom flask, add 100ml ethanol to dissolve into a uniform solution, then slowly drop isopropyl titanate, stir magnetically at 25℃ for 20h, react at 150℃ for 24h, separate, wash, dry and calcine to obtain TiO with a porous structure. 2Matrix carrier. Equimolar KH-550 and succinic anhydride were uniformly dispersed in 50 ml DMF, and magnetically stirred at 50 °C for 3 h. Then, 20 ml of porous TiO 2 The matrix carrier DMF solution was stirred for 5 h, centrifuged, washed and dried to obtain porous TiO2 modified with surface carboxyl groups. 2 Matrix carrier.

[0100] Step 2: The surface carboxyl-modified porous TiO 2 5 g of the matrix carrier was placed in a pear-shaped bottle, and 100 ml of an ethanol solution containing 5 g of diethylaminohydroxybenzoyl benzoic acid hexyl ester was added. The mixture was stirred at 50 ° C for 24 h, and then rotary evaporated at 40 ° C for 2 h and dried for 24 h to obtain a porous TiO2 with surface carboxyl modification. 2 Packed with diethylamino hydroxybenzoyl hexyl benzoate sunscreen.

[0101] Example 4

[0102] Provide a cosmetic product:

[0103] The sunscreen raw material prepared in Example 1 was added to the cosmetic formula, and the sun protection index test was performed. The specific proportions of the cosmetic formula are as follows (by weight percentage):

[0104] Phase A: 10% Cyclopentasiloxane, 10% Dimethicone, 1% Polyammonium-18 Bentonite, 4% Lauryl PEG-9 Polydimethylsiloxyethyl Dimethicone, 1% Tocopheryl Acetate, 20% Example 1.

[0105] Phase B: 10% Isododecane, 5% Methyl Methacrylate Crosspolymer, 0.05% Fragrance.

[0106] Phase C: 25% water, 3% glycerin, 3% propylene glycol, 2% triethanolamine,

[0107] Phase D: 1.95% phenoxyethanol, 5% edible ethanol.

[0108] Preparation process: Accurately weigh the raw materials of phase A and add them to the oil phase pot, fully disperse until completely dissolved, then heat to 85°C, keep warm for 10 minutes, cool to below 40°C, add the accurately weighed raw materials of phase B and stir and homogenize for 5 minutes. Accurately weigh the raw materials of phase C and add them to the water phase pot, heat to 85, keep warm for 10 minutes, cool to below 40°C, add the accurately weighed raw materials of phase D and stir for 10 minutes. Finally, slowly add the water phase to the oil phase, stir for 10 minutes, and homogenize for 3 minutes.

[0109] Example 5

[0110] Provide a cosmetic product:

[0111] The sunscreen raw material prepared in Example 2 was added to the cosmetic formula, and the sun protection index test was performed. The specific proportions of the cosmetic formula are as follows (by weight percentage):

[0112] Phase A: 10% Cyclopentasiloxane, 10% Dimethicone, 1% Polymonium-18 Bentonite, 4% Lauryl PEG-9 Polydimethylsiloxyethyl Dimethicone, 1% Tocopheryl Acetate, 20% Example 2.

[0113] Phase B: 10% Isododecane, 5% Methyl Methacrylate Crosspolymer, 0.05% Fragrance.

[0114] Phase C: 25% water, 3% glycerin, 3% propylene glycol, 2% triethanolamine,

[0115] Phase D: 1.95% phenoxyethanol, 5% edible ethanol.

[0116] Preparation process: Accurately weigh the raw materials of phase A and add them to the oil phase pot, fully disperse until completely dissolved, then heat to 85°C, keep warm for 10 minutes, cool to below 40°C, add the accurately weighed raw materials of phase B and stir and homogenize for 5 minutes. Accurately weigh the raw materials of phase C and add them to the water phase pot, heat to 85, keep warm for 10 minutes, cool to below 40°C, add the accurately weighed raw materials of phase D and stir for 10 minutes. Finally, slowly add the water phase to the oil phase, stir for 10 minutes, and homogenize for 3 minutes.

[0117] Example 6

[0118] Provide a cosmetic product:

[0119] The sunscreen raw material prepared in Example 3 was added to the cosmetic formula, and the sun protection index test was performed. The specific proportions of the cosmetic formula are as follows (by weight percentage):

[0120] Phase A: 10% Cyclopentasiloxane, 10% Dimethicone, 1% Polyammonium-18 Bentonite, 4% Lauryl PEG-9 Polydimethylsiloxyethyl Dimethicone, 1% Tocopheryl Acetate, 20% Example 3.

[0121] Phase B: 10% Isododecane, 5% Methyl Methacrylate Crosspolymer, 0.05% Fragrance.

[0122] Phase C: 25% water, 3% glycerin, 3% propylene glycol, 2% triethanolamine,

[0123] Phase D: 1.95% phenoxyethanol, 5% edible ethanol.

[0124] Preparation process: Accurately weigh the raw materials of phase A and add them to the oil phase pot, fully disperse until completely dissolved, then heat to 85°C, keep warm for 10 minutes, cool to below 40°C, add the accurately weighed raw materials of phase B and stir and homogenize for 5 minutes. Accurately weigh the raw materials of phase C and add them to the water phase pot, heat to 85, keep warm for 10 minutes, cool to below 40°C, add the accurately weighed raw materials of phase D and stir for 10 minutes. Finally, slowly add the water phase to the oil phase, stir for 10 minutes and homogenize for 3 minutes. SiO2 10%, diethylamino hydroxybenzoyl hexyl benzoate 10%.

[0125] Comparative Example 1

[0126] Provide a cosmetic product:

[0127] A sunscreen agent having the same proportion as that in Example 1 (not wrapped in a porous matrix carrier) was added to the cosmetic formula, and a sun protection index test was performed. The specific proportions of the cosmetic formula are as follows (by weight percentage):

[0128] Phase A: 10% Cyclopentasiloxane, 10% Dimethicone, 1% Polyammonium-18 Bentonite, 4% Lauryl PEG-9 Polydimethylsiloxyethyl Dimethicone, 1% Tocopheryl Acetate, 10% SiO 2 , 10% diethylamino hydroxybenzoyl hexyl benzoate.

[0129] Phase B: 10% Isododecane, 5% Methyl Methacrylate Crosspolymer, 0.05% Fragrance.

[0130] Phase C: 25% water, 3% glycerin, 3% propylene glycol, 2% triethanolamine,

[0131] Phase D: 1.95% phenoxyethanol, 5% edible ethanol.

[0132] Preparation process: Accurately weigh the raw materials of phase A and add them to the oil phase pot, fully disperse until completely dissolved, then heat to 85°C, keep warm for 10 minutes, cool to below 40°C, add the accurately weighed raw materials of phase B and stir and homogenize for 5 minutes. Accurately weigh the raw materials of phase C and add them to the water phase pot, heat to 85, keep warm for 10 minutes, cool to below 40°C, add the accurately weighed raw materials of phase D and stir for 10 minutes. Finally, slowly add the water phase to the oil phase, stir for 10 minutes, and homogenize for 3 minutes.

[0133] Comparative Example 2

[0134] Provide a cosmetic product:

[0135] A sunscreen agent having the same proportion as that in Example 2 (not encapsulated by a porous matrix carrier) was added to the cosmetic formula, and a sun protection index test was performed. The specific proportions of the cosmetic formula are as follows (by weight percentage):

[0136] Phase A: 10% Cyclopentasiloxane, 10% Dimethicone, 1% Polyammonium-18 Bentonite, 4% Lauryl PEG-9 Polydimethylsiloxyethyl Dimethicone, 1% Tocopheryl Acetate, 10% SiO 2 , 10%TiO 2 .

[0137] Phase B: 10% Isododecane, 5% Methyl Methacrylate Crosspolymer, 0.05% Fragrance.

[0138] Phase C: 25% water, 3% glycerin, 3% propylene glycol, 2% triethanolamine,

[0139] Phase D: 1.95% phenoxyethanol, 5% edible ethanol.

[0140] Preparation process: Accurately weigh the raw materials of phase A and add them to the oil phase pot, fully disperse until completely dissolved, then heat to 85°C, keep warm for 10 minutes, cool to below 40°C, add the accurately weighed raw materials of phase B and stir and homogenize for 5 minutes. Accurately weigh the raw materials of phase C and add them to the water phase pot, heat to 85, keep warm for 10 minutes, cool to below 40°C, add the accurately weighed raw materials of phase D and stir for 10 minutes. Finally, slowly add the water phase to the oil phase, stir for 10 minutes, and homogenize for 3 minutes.

[0141] Comparative Example 3

[0142] Provide a cosmetic product:

[0143] A sunscreen agent with the same proportion as that in Example 3 (not wrapped in a porous matrix carrier) was added to the cosmetic formula, and a sun protection index test was performed. The specific proportions of the cosmetic formula are as follows (by weight percentage):

[0144] Phase A: 10% Cyclopentasiloxane, 10% Dimethicone, 1% Polyammonium-18 Bentonite, 4% Lauryl PEG-9 Polydimethylsiloxyethyl Dimethicone, 1% Tocopheryl Acetate, 10% TiO 2 , 10% diethylamino hydroxybenzoyl hexyl benzoate.

[0145] Phase B: 10% Isododecane, 5% Methyl Methacrylate Crosspolymer, 0.05% Fragrance.

[0146] Phase C: 25% water, 3% glycerin, 3% propylene glycol, 2% triethanolamine,

[0147] Phase D: 1.95% phenoxyethanol, 5% edible ethanol.

[0148] Preparation process: Accurately weigh the raw materials of phase A and add them to the oil phase pot, fully disperse until completely dissolved, then heat to 85°C, keep warm for 10 minutes, cool to below 40°C, add the accurately weighed raw materials of phase B and stir and homogenize for 5 minutes. Accurately weigh the raw materials of phase C and add them to the water phase pot, heat to 85, keep warm for 10 minutes, cool to below 40°C, add the accurately weighed raw materials of phase D and stir for 10 minutes. Finally, slowly add the water phase to the oil phase, stir for 10 minutes, and homogenize for 3 minutes.

[0149] Comparative Example 4

[0150] Provided is a sunscreen raw material, which is prepared as follows:

[0151] (1) Add 0.25 g of hexadecyltrimethylammonium bromide, 25 mL of n-hexane, 30 mL of deionized water, and 15 mL of ether solution into a reaction vessel, heat to 50 °C, and stir for 20 min.

[0152] (2) Add 4 mL of ethyl orthosilicate solution and 1 mL of ammonia solution dropwise to the mixed solution in step (1), and react at 50°C for 10 h.

[0153] (3) After the reaction is completed, the mixture is centrifuged and washed, and the precipitate is calcined at 550°C for 3 hours to obtain hollow mesoporous silica nanospheres.

[0154] (4) Add 0.35 g of hollow mesoporous silica nanospheres, 40 mL of ethanol solution, and 0.17 g of sunscreen into a reaction vessel and stir at room temperature for 3 h.

[0155] (5) After the reaction is completed, centrifuge, wash, and dry at 60°C for 12 hours to obtain the final product.

[0156] Experimental Example 1

[0157] The UV transmittance of the sunscreen raw materials obtained in Example 1 and Comparative Example 4 was investigated. Figure 1 .

[0158] Figure 1 The UV transmittance test method for sunscreen raw materials uses UV-visible spectrophotometry. The instrument used is Shimadzu UV-2600 UV-visible spectrophotometer. Cut the 3M tape into 1cm×4cm size and stick it on the light-transmitting side surface of the quartz cuvette. Place the quartz cuvette with tape in the sample light path and the reference light path, and adjust the instrument zero point. Accurately weigh 8mg of the sample to be tested, and evenly apply the sample on the 3M tape of the quartz cuvette. Place the sample cuvette to be tested in the sample light path, take another quartz cell with tape and place it in the reference light path, and measure the UV transmittance curve.

[0159] Figure 1The surface carboxylic acid-modified porous SiO prepared in Example 1 is shown. 2 Comparison of the UV transmittance of the sunscreen raw material encapsulating diethylaminohydroxybenzoyl hexyl benzoate and the sunscreen raw material prepared in Comparative Example 4. Curve (a) is Example 1; curve (b) is Comparative Example 4.

[0160] from Figure 1 It can be seen that the UV transmittance of the sunscreen prepared in Example 1 is significantly lower than the UV transmittance of the sunscreen raw material in Comparative Example 4, which indicates that the sunscreen prepared in the present application has a better sunscreen effect.

[0161] Experimental Example 2

[0162] The pore structure parameters of the sunscreen raw material prepared in Example 1 were tested, and the results are shown in Table 1.

[0163] Among them, sample 1 is the porous SiO prepared in Example 1. 2 ;

[0164] Sample 2 is the surface carboxylic acid modified porous SiO prepared in Example 1. 2 Sunscreen ingredient encapsulating diethylamino hydroxybenzoyl hexyl benzoate sunscreen agent.

[0165] The pore structure parameters of samples 1 and 2 are shown in Table 1.

[0166] Table 1

[0167]

[0168] It can be seen from Table 1 that the small pores of the porous matrix carrier are mostly filled with the inclusions, and the remaining large pores may be the interstitial pores where the particles are aggregated. The information on the BET specific surface area and pore volume reduction in the table can prove that the inclusions are wrapped into the porous structure.

[0169] Experimental Example 3

[0170] The sunscreen performance of the cosmetics prepared in Examples 4-6 and Comparative Examples 1-3 was investigated, and the results are shown in Table 2. The results mainly include in vitro sun protection index evaluation (SPF and PFA).

[0171] In vitro test methods:

[0172] The instrument used for this in vitro test is the Labsphere UV-2000S UV transmittance analyzer. The sample to be tested was evenly spread on the PMMA plate, and different wavelengths of ultraviolet light (250~450nm) were used to test the absorbance of the sample. The in vitro SPF value and PFA value are shown in Table 2.

[0173] Table 2

[0174]

[0175] As can be seen from Table 2, the sun protection index of the cosmetics provided in each embodiment of the present application is significantly higher than that of the cosmetics provided in the comparative examples. The molecular weight of the sunscreens in comparative examples 1-3 is very small, and it is easy to enter the human body through the skin pores such as hair follicles, causing harm. However, by wrapping the small molecule substances, the sunscreens are prevented from directly contacting the skin, thereby avoiding the risk of sunscreens causing damage to the skin, such as irritation and oxidation.

[0176] Experimental Example 4

[0177] The wrapping effects of the sunscreen raw materials of Example 1 and Comparative Example 4 were investigated.

[0178] The surface carboxylic acid-modified porous SiO prepared in Example 1 2 The sunscreen raw material encapsulating diethylamino hydroxybenzoyl hexyl benzoate is denoted as: Sample 1; the hollow SiO prepared in Comparative Example 4 2 The sunscreen raw material loaded with ethylaminohydroxybenzoyl hexyl benzoate is recorded as: Sample 2.

[0179] Test method: Sample 1 and sample 2 were immersed in ethanol (the final mass percentage of the sample was 10%), and the supernatant was collected after standing for 1 day, 2 days and 7 days to test the content of sunscreen in the solution. Assume that the concentration of the inclusions in the sunscreen raw material is C0, and the dissolution concentration is C (the concentration can be tested by Shimadzu UV-2600 UV-visible spectrophotometer). Leakage rate: X=C / C0; the results are shown in Table 3.

[0180] Table 3

[0181]

[0182] It can be seen from Table 3 above that the leakage rate of Comparative Example 4 is very high, at 90%-99.5%; there is almost no wrapping effect; while the leakage rate of the sunscreen raw material prepared in the embodiment of the present application is very low, at 1%-2.1%; there is almost no leakage; this shows that the sunscreen raw material of the present application allows the sunscreen agent to be firmly accommodated in the porous structure of the porous matrix carrier, and it is not easy to fall off from the porous matrix carrier, thereby ensuring a reliable wrapping effect, and then being able to ensure that the sunscreen ability of the sunscreen agent is stably improved while reducing the risk of the sunscreen agent being inhaled by the skin, thereby hopefully avoiding the risk of sunscreen agent irritating the skin, oxidation and other damage. The above description is only a preferred embodiment of the present application, and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and changes. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the scope of protection of the present application.

Claims

1. A method for preparing a sunscreen raw material, characterized in that: include: Step 1: Weigh 20g of P123 into a round-bottom flask, add 400ml of 2.0M HCl solution to dissolve into a uniform solution, then slowly add TEOS, stir in a 40℃ water bath for 30min, react at 100℃ for 24h, separate, wash, dry and calcine to obtain a SiO2 matrix carrier with a hexagonal mesoporous structure; evenly disperse equimolar KH-550 and succinic anhydride in 50ml of DMF, stir magnetically at 50℃ for 3h, add 20ml of porous SiO2 matrix carrier DMF solution that has been ultrasonically dispersed for 10min to the system, continue stirring for 5h, centrifuge, wash and dry to obtain a porous SiO2 matrix carrier modified with surface carboxyl groups; Step 2: Place 5 g of the SiO2 matrix carrier with a hexagonal mesoporous structure and surface carboxyl modified obtained in step 1 in a pear-shaped bottle, add 100 ml of an ethanol solution containing 5 g of diethylaminohydroxybenzoyl hexyl benzoate, stir magnetically at 50°C for 24 h, rotary evaporate at 40°C for 2 h, and dry for 24 h to obtain a surface carboxyl modified, porous SiO2-encapsulated diethylaminohydroxybenzoyl hexyl benzoate sunscreen.

2. A sunscreen raw material, characterized in that: The sunscreen material is prepared by the preparation method of the sunscreen material according to claim 1.

3. The sunscreen raw material according to claim 2, characterized in that: The sunscreen raw material is a sunscreen raw material in which porous SiO2 modified with surface carboxylic acid encapsulates diethylamino hydroxybenzoyl hexyl benzoate.

4. The sunscreen raw material according to claim 2, characterized in that: The BET specific surface area of ​​the sunscreen raw material is 12.2 m 2 / g.

5. The sunscreen raw material according to claim 2, characterized in that: The pore size of the sunscreen material is 10.3 nm; the pore volume of the sunscreen material is 0.03 m 3 / g.

6. The sunscreen raw material according to claim 2, characterized in that: The leakage rate of the sunscreen raw material is 1%-2.1%; Wherein, the test method of the leakage rate of the sunscreen raw material is: The sunscreen raw material is immersed in ethanol to obtain a test solution with a mass percentage of 10%, and the content of the sunscreen agent in the supernatant test solution is collected after standing for 1 day, 2 days and 7 days; it is assumed that the concentration of the inclusions in the sunscreen raw material is C0 and the dissolution concentration is C; the leakage rate: X=C / C0; C and C0 are tested using a UV-visible spectrophotometer.

7. A cosmetic, characterized in that: The cosmetic comprises the sunscreen raw material according to any one of claims 2 to 6.

Citation Information

Patent Citations

  • Hollow mesoporous silicon dioxide microspheres as well as preparation method and application thereof, sun-screening agent loaded in hollow mesoporous silicon dioxide microspheres, and preparation method and an application of sun-screening agent

    CN109160519A

  • Resveratrol-containing sunscreen composition and preparation method and application thereof

    CN110772438A

  • Wet-type forming color cosmetic composition containing organic sunscreen supported in hydrophobic-treated porous silica and preparing method thereof

    KR1020140117243A